Donation type and the effect of pre-transplant donor specific antibodies – Data from the Swiss Transplant Cohort Study - de Rougemont, Olivier; Deng, Yun; Frischknecht, Lukas; Wehmeier, Caroline; Villard, Jean; Ferrari-Lacraz, Sylvie; Golshayan, Déla; Gannagé, Monique; Binet, Isabelle; Wirthmueller, Urs; Sidler, Daniel; Schachtner, Thomas; et al. (Frontiers in Immunology, 2023)
The type of donation may affect how susceptible a donor kidney is to injury from pre-existing alloimmunity. Many centers are, therefore, reluctant to perform donor specific antibody (DSA) positive transplantations in the setting of donation after circulatory death (DCD). There are, however, no large studies comparing the impact of pre-transplant DSA stratified on donation type in a cohort with a complete virtual cross-match and long-term follow-up of transplant outcome. We investigated the effect of pre-transplant DSA on the risk of rejection, graft loss, and the rate of eGFR decline in 1282 donation after brain death (DBD) transplants and compared it to 130 (DCD) and 803 living donor (LD) transplants. There was a significant worse outcome associated with pre-transplant DSA in all of the studied donation types. DSA directed against Class II HLA antigens as well as a high cumulative mean fluorescent intensity (MFI) of the detected DSA showed the strongest association with worse transplant outcome. We could not detect a significant additive negative effect of DSA in DCD transplantations in our cohort. Conversely, DSA positive DCD transplants appeared to have a slightly better outcome, possibly in part due to the lower mean fluorescent intensity (MFI) of the pre-transplant DSA. Indeed when DCD transplants were compared to DBD transplants with similar MFI (<6.5k), graft survival was not significantly different. Our results suggest that the negative impact of pre-transplant DSA on graft outcome could be similar between all donation types. This suggests that immunological risk assessment could be performed in a similar way regardless of the type of donor kidney transplantation.